Consolidação de MVs em nuvem IaaS orientada por operações elásticas e focada em consumo energético - Rück, Denivy B.; Miers, Charles C.; Pillon, Maurício A.; Koslovski, Guilherme P. (Anais do Workshop em Clouds e Aplicações (WCGA); 2017: Anais do XV Workshop em Clouds e Aplicações, 2017)
The elastic provisioning of virtual infrastructures (IVs) enable a dynamic management of cloud resources. Based on elasticity, virtual computing, storage, and communication the resources are adjusted to fit on hosted application requirements. In order to accomplish elasticity requests, providers rely on reallocation mechanisms and policies. The concern, regarding sustentability and operational costs, turns the data center power consumption a recurring theme in provider policies. Moreover, power-aware provisioning is beneficial for both tenants and providers. Thus, we propose an algorithm considering the proportional sharing of CPU usage of data center servers in order to calculate individual costs, disable idle equipments, and reallocate virtualized resources. The experimental analysis indicates a reduction of energy consumption near to 50% without impacting the acceptance ratio of new requests.